Notes from the underground ebook - Dostoyevsky, Fyodor (Duke Classics, 2012)
Notes from the Underground is Fyodor Dostoevsky's 1864 masterpiece following the ranting, slightly unhinged memoir of an isolated, anonymous civil servant. A dramatic monologue in which the narrator leaves himself open to ridicule and reveals more of his weaknesses than he intends, this influential short novel lays the ground work for the political, religious, moral and political ideas that are explored in Dostoevsky's later works.